2016
DOI: 10.1016/j.oraloncology.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Individualized risk prediction of outcomes for oral cavity cancer patients

Abstract: Background Optimal management of oral cancer relies upon accurate and individualized risk prediction of relevant clinical outcomes. Individualized prognostic calculators have been developed to guide patient–physician communication and treatment-related decision-making. However it is critical to scrutinize their accuracy prior to integrating into clinical care. Aim To compare and evaluate oral cavity cancer prognostic calculators using an independent dataset. Methods: Five prognostic calculators incorporating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…27, 46 In the current study, we found OPSCC calculators to yield higher AUCs and C-indices than did oral cavity and larynx models. This is likely due to the availability and incorporation of HPV, a robust biomarker in the OPSCC calculators.…”
Section: Discussionsupporting
confidence: 49%
“…27, 46 In the current study, we found OPSCC calculators to yield higher AUCs and C-indices than did oral cavity and larynx models. This is likely due to the availability and incorporation of HPV, a robust biomarker in the OPSCC calculators.…”
Section: Discussionsupporting
confidence: 49%
“…These findings are in agreement with previously published data. 24 The discriminatory ability of the model proposed herein is higher than that of the 5 known risk calculators for oral cavity SCC, for which the AUC ranged from 0.652 to 0.706. The AJCC decided on a checklist of 16 items necessary for their endorsement of any risk model.…”
Section: Discussionmentioning
confidence: 67%
“…For example, tumor bed sampling and the need for margin revision correlated with higher rates of LR. 24 To the best of our knowledge, none of the other oral cavity SCC models accounts for oral cavity subsite, margin status, or PNI. 11,13,21,22 A prognostic risk model for early oral tongue SCC may facilitate the prediction of LR and LRR and guide therapeutic choices after glossectomy for patients with pN0 disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess clinical prognostic tools, analyses that compare the calculators' predictions with each other and with modern observed outcomes are imperative . These validation studies are best performed on independent patient cohorts that encompass diverse geographic regions and patient demographics . The objective of the current study was to use an independent patient cohort to externally evaluate and validate published prognostic calculators designed for patients with laryngeal cancer.…”
Section: Introductionmentioning
confidence: 99%